A clinical study involving anatomical distribution, pathological patterns and differentiation degrees in population with small bowel tumor - Akulwar, Akshay; Akulwar, Anil; Rao, Siddarth; Narang, Ravinder (International Surgery Journal, 2018)
Background: Occurrence of tumor of small bowel is very rare but the burden is in growing state in both more and less economically countries because of consumption of tobacco chewing by youngsters. Methods: These studies include diagnosis and treatment of patients reported at tertiary care center of each districts of Vidarbha region and nearby districts for a schedule of six years. Results: Data refers to female predilection with male to female ratio of 0.75:1. The mean age of incidence for men and women recorded were 35+/-20.23 and 57+/-17.91 years respectively. Pain in abdomen was recorded as primary sign in 92.86% cases along with change in bowel habits in 85.71%. Anemia found was related to loss of weight and appetite. Malena and diarrhea were also significant in 65.29 and 14.95% of patients along with presence of mucus in stool in one patient. Pallor and palpable mass in abdomen were characteristic in 42.86% and 14.29% cases. Bowel wall thickening in 71.4% and bowel mass in 28.6% were examined by computer tomography. Intra-abdominal lymphadenopathy along with bowel wall thickening and bowel mass were noticed in one patient. Liver secondaries were seen in 3 patients (21.43%). Ileum was most susceptible site of tumor with development of adenocarcinoma malignancy. Conclusions: Improvement in socioeconomic background, literacy and awareness regarding causative agents helps to control percentage of incidence.